Influence of penetration force in clay soils due to speed rate effect - Ayob, Azranasmarazizi (2018)
This research discusses the effects of penetration rate on the penetration resistance in clayey soils for five different speeds of penetrations. In order to install the pile through hydraulic system, it is crucial to understand the required penetration force needed to do the job. Generally, the penetration force and speed will be different for different soil conditions. Proper understanding of this scenario may facilitate the engineer to mobilize the suitable pile installer to the construction site. Therefore, this study are to determine the influence of pile installation force in clay by conducting field cone penetration test (CPT) over a range of rates 0.5 cm/s, 1cm/s, 2cm/s, 2.5cm/s and 5cm/s. A total of fifteen point cone penetration test were conducted to determine the behaviour of the clayey soils under the different penetration loading rates. Results show that the speed for 0.5 cm/s and 1 cm/s is more accurate and more consistent compared to 2 cm/s, 2.5 cm/s and 5 cm/s. This is because with lower speed, the test becomes easier to control unlike higher speed. Besides that, maximum strength was achieved when test reach to standard speed of penetration and reducing when the rate exceeds the 2.5 cm/s speed. These findings may serve a wide range of industrial applications whereby require the solution of time domain problems and an associated understanding of rate effects in clay soils. Then, a relationship between speeds of penetration with shear strength was determined. Keyword: Speed of penetrations, cone penetration test, rate effect, shear strength